Hubungan Praktek Personal Hygiene Ibu dan Kondisi Sanitasi Lingkungan Rumah dengan Kejadian Diare pada Balita di Puskesmas Kampung Dalam Kecamatan Pontianak Timur - Kamilla, Laila; Suhartono, Suhartono; Wahyuningsih, Nur Endah (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Diarrhea has been one of severe health problems in Indonesia. A survey on household health, SKRT(2004) reported that diarrhea was the second ranked disease that caused death of under five year-old infants, andthe third ranked of the overall ages. In Kalimantan Barat, diarrhea becomes the third most dangerous disease,behind dengue and tuberculosis, to cause fatalities with the Incidence Rate of 10%. Data from the Health Office ofPontianak showed 8,374 diarrhea incidences in six districts. The frequent cases were found in Pontianak TimurRegency with 1,430 incidences. Data obtained from the Kampung Dalam Public Health Center, which is situated inPontianak Timur District, showed the highest rate of diarrhea incidence in the regency with 480 cases with prevalencerate of 33.6% (368 of them suffered by under the five year-old infants).Methode : This research aimed to find out the relationship of maternal personal hygiene and housing environmentalsanitation to diarrhea in under five year-old infants at the Public Health Center of Kampung Dalam. The researchwas performed by cross-sectional design, using 1,125 mothers with 12-59 month-old infants who lived in the servicearea of Kampung Dalam Public Health Center as population, resulting in 89 samples by a proportional randomsampling method. These data were then subject to bivariate Chi-square test and multivariate logistic regression test.Result : The overall results showed that the diarrhea incidences were suffered by 50 (56.2%) under five year-oldinfants. Most respondents had poor personal hygienic practices, as the bivariate analysis show the relationshipbetween washing hands with soap before eating (p = 0.002; RP = 1.853), washing hands with soap after going torestroom (p = 0.020; RP = 1.690), and good practices in food management (p = 0.0001; RP = 3.467) on diarrhea.The environmental conditions relating to diarrhea consisted of restroom availability (p = 0.014; RP = 2.72), SPAL(p = 0.025; RP = 4.84), and water quality (p = 0.014; RP = 1.76). However, waste bin condition (p = 0.135) andclean water source (p = 0.627) did not relate to diarrhea. The multivariate variables that became the dominant riskfactor to the diarrhea incidence on the under five year-old infants were food management good practices and healthyrestroom.Conclusion : In conclusion, good practices in food management and healthy restroom gave the diarrhea probabilityof 94%.Keywords : personal hygiene, environmental sanitation, diarrhea